Organic ammonium iodide-based electrolyte and preparation method and application thereof

By using organic ammonium iodide-based electrolyte in secondary batteries, the problems of energy density limits and scarcity of materials in lithium-ion batteries have been solved, and the electrochemical activity and stable circulation performance of the battery have been significantly improved.

CN119581673AActive Publication Date: 2025-03-07NANJING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510135220.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-07
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

The energy density of lithium-ion batteries has reached its limit, and problems such as scarcity of raw materials, dendrites formation and safety hazards have hindered their development, and new technologies beyond lithium-ion are needed.

Method used

The electrolyte solution is made by co-dissolving organic ammonium iodide and metal iodide salt in an organic solvent, and used in secondary batteries to form an organic ammonium iodide-based electrolyte solution, which significantly improves the electrochemical performance.

Benefits of technology

The electrolyte exhibits good electrochemical activity and stable cycling performance in the secondary battery, and can cyclize stably for more than 400 hours under 0.02 mA cm-2, significantly improving the energy density and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581673A_ABST
    Figure CN119581673A_ABST
Patent Text Reader

Abstract

The invention discloses an organic ammonium iodide-based electrolyte and a preparation method and application thereof. The organic ammonium iodide-based electrolyte is composed of metal iodized salt, organic ammonium iodide and an organic solvent. The organic ammonium iodide-based electrolyte is stable in property and easy to prepare, when the organic ammonium iodide-based electrolyte is applied to a secondary battery, the electrochemical performance is remarkably improved, under the current density of 0.02 mA cm <-2 >, a symmetric battery formed by the organic ammonium iodide-based electrolyte can stably circulate for more than 400 h, the overpotential is greatly reduced, and the organic ammonium iodide-based electrolyte has a wide application prospect in the field of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an organic ammonium iodide-based electrolyte and a preparation method and application thereof, belonging to the field of secondary batteries. Background Art

[0002] High energy density rechargeable lithium-ion batteries (LIBs) currently dominate the portable electronics market and the electric vehicle market due to their relatively high energy density, good cycle life and reliable performance characteristics. However, the growth of the electric vehicle market is constrained by the limited driving range achievable with lithium-ion technology, which needs to be continuously increased by increasing battery energy density. In addition, it is widely believed that lithium-ion technology has reached the limit of its energy density capabilities and new "beyond lithium-ion" technologies need to be developed. However, the scarcity of raw materials, severe dendrite formation and potential safety hazards have greatly hindered the development of lithium metal batteries (LMBs).

[0003] The study showed that, in contrast to lithium, multivalent metals such as Mg and Ca can be deposited uniformly from appropriate electrolyte solutions with little or no dendritic growth. This finding makes it possible to use multivalent metal anodes instead of the graphite anodes used in lithium-ion batteries, thereby significantly increasing the weight and volumetric capacity of the anode. This is expected to increase the energy density of these multivalent battery systems compared to lithium-ion batteries. The use of multivalent ions may also increase the electrochemical capacity of the intercalation electrodes, thereby significantly increasing the energy density of batteries using these electrodes compared to lithium-ion batteries. For example, if divalent ions such as Mg are used 2+ , Ca 2+ ), then only half as many divalent ions need to be inserted to achieve the same amount of electron transfer compared to equivalent monovalent ion intercalation. If the host structure can accommodate these divalent ions, then this can theoretically allow the electrochemical capacity of the electrode to be comparable to that of a monovalent intercalated species (e.g., Li + Or Na + ) doubled compared to the same intercalated host.

[0004] Compared with other multivalent metal ions, alkaline earth metal ions (especially calcium and magnesium ions) have attracted increasing attention due to their natural abundance, low cost and stable valence state. More specifically, calcium and magnesium are the fifth and eighth most abundant elements in the earth's crust, respectively, with widespread global resource distribution, non-toxicity and excellent thermal stability. 2+ and Mg / Mg 2+ The standard redox potential of is -2.87 V, -2.37 V (vs standard hydrogen electrode), close to Li / Li + , and the corresponding metal volume capacities are as high as 2073 mAh cm -3 and 3833 mAh cm-3 , which is conducive to achieving higher energy density.

[0005] Organic ammonium iodide is an organic iodide, which is usually used as an important material in solar cells, especially perovskite solar cells. Organic ammonium iodide is one of the key ingredients for preparing perovskite materials, and is often mixed with inorganic halides to form lead halide perovskite materials. By optimizing the content and ratio of organic ammonium iodide, the stability and efficiency of perovskite solar cells can be significantly improved. At present, there is no literature report on the application of organic ammonium iodide in secondary batteries. Summary of the invention

[0006] The purpose of the present invention is to provide an organic ammonium iodide-based electrolyte and a preparation method and application thereof. The present invention prepares an electrolyte by dissolving organic ammonium iodide and a metal iodide salt in an organic solvent to obtain an organic ammonium iodide-based electrolyte, which is applied to a secondary battery and exhibits excellent electrochemical performance.

[0007] The technical solution for achieving the purpose of the present invention is as follows:

[0008] The organic ammonium iodide-based electrolyte is composed of a metal iodide salt, organic ammonium iodide and an organic solvent.

[0009] Furthermore, the metal iodide salt is a metal iodide salt that can be used in a secondary battery, including but not limited to CaI2, MgI2, etc.

[0010] Furthermore, organic ammonium iodide includes but is not limited to methylammonium iodide, ethylammonium iodide, propylammonium iodide, butylammonium iodide, pentylammonium iodide and the like.

[0011] Furthermore, the organic solvent is an organic solvent commonly used in secondary batteries, including but not limited to ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and the like.

[0012] Furthermore, in the organic ammonium iodide-based electrolyte, the concentration of organic ammonium iodide is 0.01-0.8 mol L -1 .

[0013] Furthermore, in the organic ammonium iodide-based electrolyte, the concentration of metal iodide salt is 0.01-0.05 mol L -1 .

[0014] In one embodiment of the present invention, the organic ammonium iodide-based electrolyte has an organic ammonium iodide concentration of 0.1 mol L -1 , the concentration of metal iodide salt is 0.05 mol L -1 .

[0015] The method for preparing the organic ammonium iodide-based electrolyte comprises the following steps:

[0016] The metal iodide salt and organic ammonium iodide are mixed and dissolved in an organic solvent, and water is removed by using a molecular sieve to obtain an organic ammonium iodide-based electrolyte.

[0017] Furthermore, the time for removing water by molecular sieve is 48~72 h.

[0018] The present invention provides the use of the organic ammonium iodide-based electrolyte as an electrolyte in a secondary battery.

[0019] Furthermore, the secondary battery is a common secondary battery in the art, including but not limited to a calcium metal battery, a magnesium metal battery, and the like.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] The present invention introduces metal iodide salt and organic ammonium iodide into the electrolyte. Due to the decomposition of the organic ammonium iodide in the battery, a layer of nitrogen-containing compounds is formed in situ on the metal surface, thereby reducing the impedance in the metal ion transmission process. The button battery assembled with the organic ammonium iodide-based electrolyte of the present invention exhibits good electrochemical activity. In addition, at 0.02 mA cm -2 Under the conditions of , the symmetrical battery composed of organic ammonium iodide-based electrolyte can stably cycle for more than 400 h, with excellent stable cycling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The electrolyte of ethylammonium iodide containing CaI2 in Example 1 1 H-NMR spectrum.

[0023] Figure 2 This is the laser confocal microscopic Raman spectrum of the ethylammonium iodide electrolyte containing CaI2 in Example 1.

[0024] Figure 3 This is the infrared spectrum of the ethylammonium iodide electrolyte containing CaI2 in Example 1.

[0025] Figure 4 This is the UV-visible spectrum of the ethylammonium iodide electrolyte containing CaI2 in Example 1.

[0026] Figure 5 This is a diagram of the relative content of elements on the surface of the electrode of the symmetrical battery containing ethylammonium iodide electrolyte containing CaI2 in Example 1 after being sputtered by argon ions for 90 seconds.

[0027] Figure 6 The symmetrical cell containing CaI2 in the ethylammonium iodide electrolyte of Example 1 at 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0028] Figure 7 This is a graph showing the cycle test results of the symmetrical battery containing CaI2-containing ethylammonium iodide electrolyte at different current densities in Example 1.

[0029] Figure 8 This is the spectrum of the 50th CV test of the symmetrical battery containing CaI2-containing ethylammonium iodide electrolyte in Example 1.

[0030] Fig. 9 This is the EIS test spectrum of the symmetrical battery containing CaI2-containing ethylammonium iodide electrolyte after 400 cycles in Example 1.

[0031] Fig.10 The calcium-copper asymmetric battery containing ethylammonium iodide electrolyte containing CaI2 in Example 1 was 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0032] Fig.11 The Ca(TFSI)2 electrolyte symmetric battery in Comparative Example 1 was used at 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0033] Fig.12 The Ca(TFSI)2 electrolyte calcium-copper asymmetric battery in Comparative Example 1 was used at 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0034] Fig.13 The CaI2 electrolyte symmetric cell in Comparative Example 2 was used at 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0035] Fig.14 The CaI2 electrolyte calcium-copper asymmetric battery in Comparative Example 2 was 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0036] Fig.15 The symmetrical cell of the low concentration ethylammonium iodide electrolyte containing CaI2 in Example 2 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0037] Fig.16 The low concentration of ethylammonium iodide electrolyte calcium-copper asymmetric battery containing CaI2 in Example 2 is 0.02 mAcm -2 Plot of Coulombic efficiency at different current densities.

[0038] Fig.17 The symmetrical cell of the high concentration ethylammonium iodide electrolyte containing CaI2 in Example 3 was-2 Graph of the results of the room temperature cycle test under current density.

[0039] Fig.18 The high concentration of ethylammonium iodide electrolyte containing CaI2 in Example 3 is a calcium-copper asymmetric battery at 0.02 mAcm -2 Plot of Coulombic efficiency at different current densities.

[0040] Fig.19 The symmetrical cell of ethylammonium iodide electrolyte containing low concentration of CaI2 in Example 4 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0041] Fig. 20 The calcium-copper asymmetric battery of ethylammonium iodide electrolyte containing low concentration of CaI2 in Example 4 is 0.02 mAcm -2 Plot of Coulombic efficiency at different current densities.

[0042] Fig.21 The symmetrical cell containing CaI2 in the methylammonium iodide electrolyte of Example 5 is 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0043] Fig. 22 The calcium-copper asymmetric battery containing methylammonium iodide electrolyte containing CaI2 in Example 5 was 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0044] Fig.23 The symmetrical cell containing CaI2 in the propylammonium iodide electrolyte of Example 6 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0045] Fig.24 The calcium-copper asymmetric battery containing CaI2 in the propylammonium iodide electrolyte of Example 6 was 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0046] Fig.25 The symmetrical cell containing CaI2 in the butylammonium iodide electrolyte of Example 7 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0047] Fig.26 The butylammonium iodide electrolyte calcium-copper asymmetric cell containing CaI2 in Example 7 is 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0048] Fig. 27The symmetrical cell containing amyl ammonium iodide electrolyte containing CaI2 in Example 8 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0049] Fig.28 The calcium-copper asymmetric battery containing amyl ammonium iodide electrolyte containing CaI2 in Example 8 was 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0050] Fig.29 The symmetrical cell of the CaI2-containing ethylammonium iodide diethylene glycol dimethyl ether electrolyte in Example 9 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0051] Fig.30 The calcium-copper asymmetric battery containing CaI2 in the ethylammonium iodide diethylene glycol dimethyl ether electrolyte in Example 9 was 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0052] Fig.31 The symmetrical cell of the CaI2-containing tetrahydrofuran ethylammonium iodide electrolyte in Example 10 was 0.02 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0053] Fig.32 The calcium-copper asymmetric cell containing CaI2 in tetrahydrofuran electrolyte at 0.02 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0054] Fig.33 For the MgI2 electrolyte symmetric cell in Comparative Example 3 at 0.1 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0055] Fig.34 The MgI2 electrolyte calcium-copper asymmetric battery in Comparative Example 3 was used at 0.1 mA cm -2 Plot of Coulombic efficiency at different current densities.

[0056] Fig.35 The symmetrical cell of ethylammonium iodide electrolyte containing MgI2 in Example 11 at 0.1 mA cm -2 Graph of the results of the room temperature cycle test under current density.

[0057] Fig.36 The calcium-copper asymmetric cell of ethylammonium iodide electrolyte containing MgI2 in Example 11 was 0.1 mA cm -2 Plot of Coulombic efficiency at different current densities. DETAILED DESCRIPTION

[0058] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] Example 1

[0060] Weigh 147 mg (0.5 mmol) of CaI2 and 173 mg (1 mmol) of ethylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain ethylammonium iodide electrolyte containing CaI2.

[0061] Figure 1 Ethyl ammonium iodide electrolyte containing CaI2 1 H-NMR spectrum. δ=3.21 ppm belongs to the -CH3 peak of the solvent ethylene glycol dimethyl ether, δ=3.56 ppm belongs to the -CH2 peak of the solvent ethylene glycol dimethyl ether, and δ=7.29 ppm belongs to the -NH3 peak of ethylammonium iodide. Figure 2 This is the laser confocal microscopic Raman spectrum of ethylammonium iodide electrolyte containing CaI2, located at 900~1100cm -1 A group of Raman peaks in the range are the CO stretching vibration peaks of different ethylene glycol dimethyl ethers, located at 800~900 cm -1 A group of Raman peaks in the range are CH2 bending vibration peaks of different ethylene glycol dimethyl ethers, located at 300~370 cm -1 A group of Raman peaks in the range are COC bending vibration peaks of different ethylene glycol dimethyl ethers, located at 390~600 cm -1 A group of Raman peaks in the range are OCC bending vibration peaks of different ethylene glycol dimethyl ethers. Figure 3 This is the infrared spectrum of ethylammonium iodide electrolyte containing CaI2, located at 2800~3000 cm -1 A group of infrared absorption peaks in the range are attributed to the stretching vibration of ethylene glycol dimethyl ether CH and ethylammonium iodide NH. Figure 4 This is the UV-visible spectrum of the ethylammonium iodide electrolyte containing CaI2. The near-ultraviolet absorption peaks at 300 nm and 380 nm are attributed to I - This proves that CaI2 and ethylammonium iodide are successfully dissolved in ethylene glycol dimethyl ether. Figure 5This is the relative content diagram of the elements on the surface of the symmetrical battery electrode after argon ion sputtering for 90 seconds. The relative content of nitrogen is 5%, proving that nitride is formed on the electrode surface.

[0062] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive and negative electrode sheets used were calcium metal discs with a diameter of 12 mm or copper foils with a diameter of 19 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100°C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0063] Figure 6 Symmetric cell with CaI2-containing ethylammonium iodide electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that 0.02 mA cm -2 , 0.02 mAh cm -2 Under the optimal conditions, it can be cycled stably for more than 400 h with an overpotential of only about 0.5 V. Figure 7 The results of the cycle test of the symmetrical battery containing CaI2 ethylammonium iodide electrolyte at different current densities are shown in Figure 2. -2 It can remain stable at all current densities, indicating that the battery has a good cycle life and will not decompose excessively under high current.

[0064] Figure 8 This is the 50th CV spectrum of the symmetrical cell containing CaI2 in ethylammonium iodide electrolyte, with a scan rate of 5 mV s -1 , voltage range -0.5~0.5 V. It can be seen that it can still remain stable after 50 cycles of testing. Fig. 9 This is the EIS test spectrum of the symmetrical battery with CaI2-containing ethylammonium iodide electrolyte after 400 cycles, with a frequency range of 100 kHz~10 mHz and an amplitude of 10 mV. It can be seen that it can still remain stable after 400 cycles, indicating that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0065] An asymmetric cell was assembled using ethylammonium iodide electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency after 100 cycles under the test conditions is as follows Fig.10 As shown, after 100 cycles, its coulombic efficiency is still 78%, indicating that the electrolyte plays a good role in extending the battery life.

[0066] Comparative Example 1

[0067] Only Ca(TFSI)2 was used as the electrolyte salt, and the Ca(TFSI)2 electrolyte was prepared by referring to the steps in Example 1, and the battery was assembled and tested. The details are as follows:

[0068] Weigh 600 mg (1 mmol) of Ca(TFSI)2 and add it to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve it. Add molecular sieves and let it stand for 48 hours to remove excess water to obtain a Ca(TFSI)2 electrolyte.

[0069] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100°C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0070] Fig.11 Symmetric cell with Ca(TFSI)2 electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under these conditions, the cycle can only last for 9 h, and the overpotential exceeds 2 V.

[0071] An asymmetric battery was assembled using Ca(TFSI)2 electrolyte, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.12 As shown, the Coulomb efficiency is only 5%.

[0072] Comparative Example 2

[0073] Only CaI2 was used as the electrolyte salt, and the CaI2 electrolyte was prepared by referring to the steps in Example 1, and the battery was assembled and tested. The details are as follows:

[0074] Weigh 147 mg (0.5 mmol) of CaI2 and add it to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve it. Add molecular sieves and let it stand for 48 hours to remove excess water to obtain a CaI2 electrolyte.

[0075] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0076] Fig.13 Symmetric cell in CaI2 electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under these conditions, the cycle overpotential increases rapidly and can only be cycled for 60 hours.

[0077] An asymmetric battery was assembled using CaI2 electrolyte, calcium metal sheet as the negative electrode, and copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.14 As shown, the Coulomb efficiency is only 8%.

[0078] Example 2

[0079] This example is basically the same as Example 1, except that the concentration of ethylammonium iodide is reduced to 0.01 mol L -1 , prepare a low concentration ethylammonium iodide electrolyte containing CaI2 by referring to the steps in Example 1, assemble the battery and test it. The details are as follows:

[0080] Weigh 147 mg (0.5 mmol) of CaI2 and 17 mg (0.1 mmol) of ethylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain a low-concentration ethylammonium iodide electrolyte containing CaI2.

[0081] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0082] Fig.15 The symmetric cell of low concentration ethylammonium iodide electrolyte containing CaI2 at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under these conditions, the overpotential increases to nearly 1 V, but the cycle can still exceed 40 h and the cycle overpotential remains stable.

[0083] An asymmetric battery was assembled using a low-concentration ethylammonium iodide electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.16 As shown, the Coulombic efficiency is 35%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte.

[0084] Example 3

[0085] This example is basically the same as Example 1, except that the concentration of ethylammonium iodide is increased to 0.8 mol / L -1 , prepare a high concentration of ethylammonium iodide electrolyte containing CaI2 by referring to the steps in Example 1, assemble the battery and test it. The details are as follows:

[0086] Weigh 147 mg (0.5 mmol) of CaI2 and 1384 mg (8 mmol) of ethylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain a high-concentration ethylammonium iodide electrolyte containing CaI2.

[0087] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0088] Fig.17 Symmetric cell with high concentration of ethylammonium iodide electrolyte containing CaI2 at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under these conditions, the overpotential increases to nearly 1 V and can be stably cycled for more than 200 times.

[0089] An asymmetric battery was assembled using a high-concentration ethylammonium iodide electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.18 As shown, the coulombic efficiency is 40%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte.

[0090] Example 4

[0091] This example is basically the same as Example 1, except that the concentration of CaI2 is reduced to 0.01 mol L -1 , prepare an ethylammonium iodide electrolyte containing low concentration of CaI2 by referring to the steps in Example 1, assemble the battery and test it. The details are as follows:

[0092] Weigh 29 mg (0.1 mmol) of CaI2 and 173 mg (1 mmol) of ethylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain an ethylammonium iodide electrolyte containing a low concentration of CaI2.

[0093] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0094] Fig.19 The symmetric cell of ethylammonium iodide electrolyte containing low concentration of CaI2 at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the same conditions, it can cycle for 50 h, and the cycle overpotential is maintained at 0.5 V within 40 h.

[0095] An asymmetric battery was assembled using an ethylammonium iodide electrolyte containing low concentration of CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig. 20 As shown, the coulombic efficiency is 20%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte.

[0096] Example 5

[0097] This embodiment is basically the same as the embodiment 1, except that the organic ammonium iodide is replaced with methylammonium iodide, and the methylammonium iodide electrolyte containing CaI2 is prepared with reference to the steps in the embodiment 1, and a battery is assembled for testing. The details are as follows:

[0098] Weigh 147 mg (0.5 mmol) of CaI2 and 159 mg (1 mmol) of methylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain a methylammonium iodide electrolyte containing CaI2.

[0099] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0100] Fig.21 Symmetric cell with CaI2-containing methylammonium iodide electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the optimal conditions, it can cycle stably for 400 h, and the overpotential is only about 0.5 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0101] An asymmetric battery was assembled using methylammonium iodide electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig. 22 As shown, the coulombic efficiency is 75%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte, indicating that the electrolyte plays a good role in extending the battery life.

[0102] Example 6

[0103] This embodiment is basically the same as the embodiment 1, except that the organic ammonium iodide is replaced with propyl ammonium iodide, and the propyl ammonium iodide electrolyte containing CaI2 is prepared with reference to the steps in the embodiment 1, and a battery is assembled for testing. The details are as follows:

[0104] Weigh 147 mg (0.5 mmol) of CaI2 and 187 mg (1 mmol) of propylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain a propylammonium iodide electrolyte containing CaI2.

[0105] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0106] Fig.23 Symmetric cell with CaI2-containing propylammonium iodide electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the optimal conditions, it can cycle stably for 400 h, and the overpotential is only about 0.5 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0107] An asymmetric cell was assembled using CaI2-containing propylammonium iodide electrolyte, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.24 As shown, the coulombic efficiency is 75%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte, indicating that the electrolyte plays a good role in extending the battery life.

[0108] Example 7

[0109] This embodiment is basically the same as the embodiment 1, except that only the organic ammonium iodide is replaced with butyl ammonium iodide, and the butyl ammonium iodide electrolyte containing CaI2 is prepared with reference to the steps in the embodiment 1, and a battery is assembled for testing. The details are as follows:

[0110] Weigh 147 mg (0.5 mmol) of CaI2 and 201 mg (1 mmol) of butylammonium iodide and add them into 10 mL of ethylene glycol dimethyl ether respectively. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain butylammonium iodide electrolyte containing CaI2.

[0111] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0112] Fig.25 Symmetric cell with CaI2-containing butylammonium iodide electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the optimal conditions, it can cycle stably for 400 h, and the overpotential is only about 0.5 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0113] An asymmetric cell was assembled using butylammonium iodide electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.26 As shown, the coulombic efficiency is 75%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte, indicating that the electrolyte plays a good role in extending the battery life.

[0114] Example 8

[0115] This embodiment is basically the same as the embodiment 1, except that the organic ammonium iodide is replaced with amyl ammonium iodide, and the amyl ammonium iodide electrolyte containing CaI2 is prepared with reference to the steps in the embodiment 1, and the battery is assembled for testing. The details are as follows:

[0116] Weigh 147 mg (0.5 mmol) of CaI2 and 215 mg (1 mmol) of amyl ammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain an amyl ammonium iodide electrolyte containing CaI2.

[0117] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0118] Fig. 27 Symmetric cell with amyl ammonium iodide electrolyte containing CaI2 at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the optimal conditions, it can cycle stably for 400 h, and the overpotential is only about 0.5 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0119] An asymmetric cell was assembled using amyl ammonium iodide electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.28 As shown, the coulombic efficiency is 75%, indicating that the electrolyte plays a good role in extending the battery life.

[0120] Example 9

[0121] This embodiment is basically the same as the embodiment 1, except that the organic solvent is replaced with diethylene glycol dimethyl ether, and the ethyl ammonium iodide diethylene glycol dimethyl ether electrolyte containing CaI2 is prepared with reference to the steps in the embodiment 1, and a battery is assembled for testing. The details are as follows:

[0122] Weigh 147 mg (0.5 mmol) of CaI2 and 173 mg (1 mmol) of ethylammonium iodide and add them to 10 mL of diethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain ethylammonium iodide diethylene glycol dimethyl ether electrolyte containing CaI2.

[0123] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0124] Fig.29 Symmetric cell with CaI2-containing ethylammonium iodide diethylene glycol dimethyl ether electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the same conditions, it can cycle stably for 150 h, and the overpotential is only about 0.5 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0125] An asymmetric battery was assembled using ethylammonium iodide diethylene glycol dimethyl ether electrolyte containing CaI2, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.30 As shown, the coulombic efficiency is 70%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte, indicating that the electrolyte plays a good role in extending the battery life.

[0126] Example 10

[0127] This example is basically the same as Example 1, except that the organic solvent is replaced with tetrahydrofuran, and the ethylammonium iodide tetrahydrofuran electrolyte containing CaI2 is prepared with reference to the steps in Example 1, and a battery is assembled for testing. The details are as follows:

[0128] Weigh 147 mg (0.5 mmol) of CaI2 and 173 mg (1 mmol) of ethylammonium iodide and add them to 10 mL of tetrahydrofuran. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain ethylammonium iodide tetrahydrofuran electrolyte containing CaI2.

[0129] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a calcium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a calcium metal disc with a diameter of 12 mm. The calcium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0130] Fig.31 Symmetric cell with CaI2-containing ethylammonium iodide tetrahydrofuran electrolyte at 0.02 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.02 mA cm -2 , 0.02 mAh cm -2 Under the optimal conditions, the battery can be cycled stably for 200 h with an overpotential of only about 0.7 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0131] An asymmetric cell was assembled using CaI2-containing ethylammonium iodide tetrahydrofuran electrolyte, a calcium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.32 As shown, the coulombic efficiency is 55%, which is significantly improved compared with CaI2 electrolyte and Ca(TFSI)2 electrolyte, indicating that the electrolyte plays a good role in extending the battery life.

[0132] Comparative Example 3

[0133] Only MgI2 was used as the electrolyte salt, and the MgI2 electrolyte was prepared by referring to the steps in Example 1, and the battery was assembled and tested. The details are as follows:

[0134] Weigh 139 mg (0.5 mmol) of MgI2 and add it to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve it. Add molecular sieves and let it stand for 48 hours to remove excess water to obtain MgI2 electrolyte.

[0135] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a magnesium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a magnesium metal disc with a diameter of 12 mm. The magnesium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0136] Fig.33 Symmetric cell with MgI2 electrolyte at 0.1 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that the battery reaches the safety cut-off voltage of -5V immediately after the discharge begins, proving that it cannot operate under this condition.

[0137] An asymmetric battery was assembled using MgI2 electrolyte, magnesium metal sheet as the negative electrode, and copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.34 As shown, it can be seen that the battery reaches a safety cutoff voltage of -5V immediately after the discharge begins, proving that it cannot operate under this condition.

[0138] Embodiment 11

[0139] This embodiment is basically the same as the embodiment 1, except that the metal iodide salt is replaced with MgI2, the calcium metal sheet is replaced with a magnesium metal sheet, and the ethylammonium iodide electrolyte containing MgI2 is prepared with reference to the steps in the embodiment 1, and a battery is assembled for testing. The details are as follows:

[0140] Weigh 139 mg (0.5 mmol) of CaI2 and 173 mg (1 mmol) of ethylammonium iodide and add them to 10 mL of ethylene glycol dimethyl ether. Stir and mix evenly at room temperature to dissolve them. Add molecular sieves and let stand for 48 h to remove excess water to obtain ethylammonium iodide tetrahydrofuran electrolyte containing MgI2.

[0141] The button cell (CR2032) was assembled from bottom to top in a glove box filled with argon in the order of "positive electrode shell → positive electrode → diaphragm → negative electrode → gasket → shrapnel → negative electrode shell" for battery performance testing. The positive electrode sheet used was a magnesium metal disc with a diameter of 12 mm or a copper foil with a diameter of 19 mm, and the negative electrode sheet used was a magnesium metal disc with a diameter of 12 mm. The magnesium metal sheet was polished with sandpaper before use. The diaphragm used was cut into discs with a diameter of 19 mm using a cutting machine and dried in a vacuum dryer at 100 °C for 12 h before use. The electrolyte injection volume used was 0.15 mL.

[0142] Fig.35 Symmetric cell with MgI2-containing ethylammonium iodide electrolyte at 0.1 mA cm -2 The results of the room temperature cycle test under current density. It can be seen that at 0.1 mA cm -2 , 0.1 mAh cm -2 Under the optimal conditions, the battery can be cycled stably for more than 200 h, and the initial overpotential is only about 0.5 V, which proves that the electrolyte plays a good role in improving the electrochemical activity and stability of the battery.

[0143] An asymmetric cell was assembled using ethylammonium iodide electrolyte containing MgI2, a magnesium metal sheet as the negative electrode, and a copper foil as the positive electrode. -2 The coulombic efficiency under the test conditions is Fig.36 As shown, the coulombic efficiency is 20%, which is significantly improved compared with MgI2 electrolyte.

[0144] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. An organic ammonium iodide-based electrolyte, characterized in that: It consists of metal iodine salt, organic ammonium iodide and organic solvent.

2. The organic ammonium iodide-based electrolyte according to claim 1, characterized in that: The metal iodide salt is CaI2 or MgI2.

3. The organic ammonium iodide-based electrolyte according to claim 1, characterized in that: The organic ammonium iodide is methylammonium iodide, ethylammonium iodide, propylammonium iodide, butylammonium iodide or pentylammonium iodide.

4. The organic ammonium iodide-based electrolyte according to claim 1, characterized in that: The organic solvent is ethylene glycol dimethyl ether, diethylene glycol dimethyl ether or tetrahydrofuran.

5. The organic ammonium iodide-based electrolyte according to claim 1, characterized in that In organic ammonium iodide-based electrolyte, the concentration of organic ammonium iodide is 0.01~0.8 mol L -1 , the concentration of metal iodide salt is 0.01~0.05 mol L -1 .

6. The organic ammonium iodide-based electrolyte according to claim 1, characterized in that In the organic ammonium iodide-based electrolyte, the concentration of organic ammonium iodide is 0.1 mol L -1 , the concentration of metal iodide salt is 0.05 mol L -1 .

7. The method for preparing the organic ammonium iodide-based electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: The metal iodide salt and organic ammonium iodide are mixed and dissolved in an organic solvent, and water is removed by using a molecular sieve to obtain an organic ammonium iodide-based electrolyte.

8. The preparation method according to claim 7, characterized in that The time for molecular sieve to remove water is 48~72 h.

9. Use of the organic ammonium iodide-based electrolyte according to any one of claims 1 to 6 as an electrolyte in a secondary battery.

10. The use according to claim 9, characterized in that: The secondary battery is a calcium metal battery or a magnesium metal battery.

Citation Information

Patent Citations

  • Battery taking iodine-containing ionic liquid as positive electrode active material and assembling method thereof

    CN107666016A

  • Electrolyte and electrochemical device

    CN112970131A

  • Magnesium metal secondary battery negative electrode surface modification method, modified magnesium metal negative electrode and battery

    CN115440938A

  • Organic lithium-iodine battery based on two-electron transfer mechanism as well as manufacturing method and application of organic lithium-iodine battery

    CN116264316A

  • Battery cell, battery and electric device

    WO2024077513A1